Health and safety: vulnerable elderly: exploring the psychological needs, mitigation behaviours and resilient in post disaster - Asrenee, Ab Razak (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2017)
The elderly are vulnerable to psychological sequels after disaster. In order to understand the disastrous on elderly psychological wellbeing, an exploratory mixed method research approach was employed in the worst htt area of 2014-Malaysian flood disaster. 156 elderly aged 60 and more, were interviewed with post flood survey, Malay Geriatric Depression Scale (M-GDS15), Malay Impact Event Scale- Revised (M-IES-R) and WHOQoL-BREF. Three focus group discussions were done to explore resilient factors. The quantitative data were analyzed using Pearson correlation and multiple linear regression analysis and qualitative data with thematic analysis. Triangulation was done to generate final resu~. Result showed 35.30% experienced traumatic stress, 41.29% depressive symptoms with 23.20% fulfilled criteria for major depression. Depression was associated with low education level and no previous history with a flood. Younger old age and sustained physical injury during flood were negative predictors for traumatic stress, and the duration of involvement with flood predicts the behavioral distress. Majority (94.90%) perceived good QoL. Depression is moderately correlated with post-traumatic stress (r = 0.342, p< 0.001 ), but negatively correlated with level of QoL in physical wellbeing (r= -0.445, p< 0.001) and psychological status (r= -0.440, p< 0.001 ). Themes related to psychological sequels were unpreparedness and low risk perception. The community cohesiveness and communal help emerged as resilient themes strengthen the positive attitudes, emotion regulation and spirituality. Therefore the communal factors are recommended to be empowered in the disaster preparedness measures.